2020
DOI: 10.4103/jehp.jehp_635_19
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral determinants of brucellosis incidence among stockbreeders and their family members in rural area based on PRECEDE model

Abstract: INTRODUCTION: Brucellosis is one of the common diseases between humans and animals. The purpose of this study was to investigate behavioral determinants of brucellosis incidence among stockbreeders and their family members in a rural area based on the PRECEDE model. MATERIALS AND METHODS: This cross-sectional study was carried out among 540 stockbreeders and their family members in Northeastern Iran in 2019. Sampling was done in two stages including stratified sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Alizadeh-Siuki et al, in a study based on PRECEDE model reported a direct and significant relationship between the preventive behaviors and reinforcing factors. 16 The results of the present study revealed that the participants did not perform well in the field of brucellosis prevention behaviors and only 54% of the maximum performance score was obtained.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Alizadeh-Siuki et al, in a study based on PRECEDE model reported a direct and significant relationship between the preventive behaviors and reinforcing factors. 16 The results of the present study revealed that the participants did not perform well in the field of brucellosis prevention behaviors and only 54% of the maximum performance score was obtained.…”
Section: Discussionmentioning
confidence: 53%
“…This result indicates that increasing social support from family members, providing education through the department of agriculture, as well as support and consensus of colleagues, can promote preventive behavior. Alizadeh‐Siuki et al, in a study based on PRECEDE model reported a direct and significant relationship between the preventive behaviors and reinforcing factors 16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnant women, occupation that requires long contact with livestock and their products, and individuals who have compromised immune systems, like cancer patients, transplant recipients receiving immunosuppressive therapy, and people with AIDS, are at risk for getting the infection. [ 34 35 ]…”
Section: Discussionmentioning
confidence: 99%